Analysis of the effects of acetyl tributyl citrate on bone cancer based on network toxicology and molecular docking - Jiang, Lujun; Shen, Juncheng; Yang, Jinghong; Wang, Zi; Tang, Lian; Li, Yuqi; Liu, Jialin; Li, Zhong; Liu, Yanshi (Frontiers in Medicine, 2025)
BackgroundAcetyl tributyl citrate (ATBC) is a widely used environmental plasticizer that has raised concerns regarding its potential health effects, particularly its role in cancer development. Although ATBC is generally considered to have a safer profile compared to traditional phthalate-based plasticizers, research on its association with bone cancer remains limited. The aim of this study is to elucidate the complex effects of Acetyl tributyl citrate (ATBC) on bone cancer and to unravel the potential molecular mechanisms by which environmental pollutants influence the disease process.MethodsThis study utilized multiple online databases to identify target genes associated with ATBC and bone cancer. Initially, protein–protein interaction (PPI) analysis and visualization of the intersecting genes were performed. Subsequently, gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analyses were conducted to explore the underlying mechanisms connecting the two conditions. Finally, molecular docking was employed to validate the interactions between these compounds and their respective targets.ResultsUsing the CHEMBL, SwissTarget Prediction, and TargetNet databases, we screened 193 genes associated with ATBC. Additionally, we identified 4,439 genes related to bone cancer through the GeneCards, OMIM, and TTD databases, resulting in 73 intersecting genes. After rigorous refinement utilizing the STRING platform and Cytoscape software, we identified five core targets: STAT3, EGFR, MMP9, MAPK1, and MMP2. Functional enrichment analysis indicated that the core targets of ATBC’s influence on bone cancer are primarily involved in the regulation of apoptosis, carcinogenesis, and cellular proliferation, among other biological processes. Finally, molecular docking simulations conducted with AutoDock confirmed robust binding interactions between ATBC and these core targets, thereby enhancing our understanding of their interactions.ConclusionThis study underscores the potential carcinogenic effects of ATBC in bone cancer, identifying key targets such as STAT3, EGFR, MMP9, MAPK1, and MMP2. The findings indicate that ATBC may facilitate the progression of bone cancer by targeting essential signaling pathways and remodeling the tumor microenvironment. This emphasizes the necessity for further research into the environmental risks associated with this plasticizer.